2009
DOI: 10.1002/chem.200902110
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Theoretical and Experimental Investigation on the Enantioselective Oxidation of Aryl Benzyl Sulfides in the Presence of a Chiral Titanium Catalyst

Abstract: An experimental investigation of the enantioselective oxidation of aryl benzyl sulfides by tert-butyl hydroperoxide in the presence of a titanium/hydrobenzoin catalyst has shown that these sulfides are ideal substrates for this catalytic system, with negligible interference by the substituents on the aryl groups. A reaction mechanism based on DFT computations has been proposed. The DFT MPWB1K functional was used in the theoretical investigation to account for weak hydrogen-bonding and pi interactions. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 64 publications
9
77
0
1
Order By: Relevance
“…[101] Frühere Arbeiten zeigten, dass aromatische T-förmige Edge-to-Face-Wechselwirkungen in enantioselektiven Reduktionen eine bedeutende Rolle spielen können. [102] Ein Effekt dieser Wechselwirkungen auf die Ausbeute und/oder Selektivität wurde für unterschiedliche Transformationen vorgeschlagen: intra-und intermolekulare photochemische Reaktionen, [103] allylische Oxidationen, [104] Ruthenium-katalysierte Transferhydrierungen, [105] Titan-katalysierte Oxidationen von Sulfiden [106] und andere. [107] Zwei Beispiele illustrieren diese Fortschritte (Abbildung 8).…”
Section: Aren-aren-wechselwirkungen In Der Organischen Syntheseunclassified
“…[101] Frühere Arbeiten zeigten, dass aromatische T-förmige Edge-to-Face-Wechselwirkungen in enantioselektiven Reduktionen eine bedeutende Rolle spielen können. [102] Ein Effekt dieser Wechselwirkungen auf die Ausbeute und/oder Selektivität wurde für unterschiedliche Transformationen vorgeschlagen: intra-und intermolekulare photochemische Reaktionen, [103] allylische Oxidationen, [104] Ruthenium-katalysierte Transferhydrierungen, [105] Titan-katalysierte Oxidationen von Sulfiden [106] und andere. [107] Zwei Beispiele illustrieren diese Fortschritte (Abbildung 8).…”
Section: Aren-aren-wechselwirkungen In Der Organischen Syntheseunclassified
“…[7,8] For many years, titanium catalyst chemistry in the oxidation of sulfides has focused mainly on the synthetic aspects, whereas mechanistic investigations have seldom been reported. [11][12][13] However, in 2009, three similar studies [6,14,15] on titanium-catalyzed enantioselective oxidation of sulfides were published, two of them [6,15] also considered theoretical aspects.…”
Section: Introductionmentioning
confidence: 96%
“…[16] Enantiopure (S)-omeprazole was obtained when (1R,2R)-1,2-bis(2-bromophenyl)ethane-1,2-diol was used as a ligand of the titanium. [14] Our contribution to the same topic was represented by a combined theoretical and experimental investigation [15] of the highly enantioselective TBHP oxidation of aryl benzyl sulfides in the presence of a complex between titanium and hydrobenzoin. [16] In the contribution, we described our most recent research on the application of this oxidation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…-is a water soluble species, and it was confirmed by 51 V NMR that its concentration increased when the oxidant was added rapidly. 94 Ellman et al investigated whether the effects seen due to different addition rates were influenced by the nature of the solvent.…”
Section: Scheme 33mentioning
confidence: 91%
“…Bolm speculated that the oxidising species formed in this oxidation were vanadium(V) species having oxoperoxy groups 90. 97 Bryliakov conducted a more extensive investigation of the vanadium species formed using 51 V NMR analysis and found that the monoperoxy species formed can exist in more than one form. 98 Two principal species were proposed to be present in equilibrium with each other -an unchelated form 91 and a chelated form 92, in which the primary alcohol coordinates to the vanadium (Scheme 34).…”
Section: Scheme 33mentioning
confidence: 99%